Math Problem Statement

Solve the equation 6 - 6x = 5x - 9x - 2.

Solution

Let's solve the equation shown in the image:

66x=5x9x26 - 6x = 5x - 9x - 2

Step 1: Simplify both sides of the equation.

On the right-hand side, simplify the terms involving xx: 5x9x=4x5x - 9x = -4x So the equation becomes: 66x=4x26 - 6x = -4x - 2

Step 2: Move all the xx-terms to one side.

Add 6x6x to both sides: 6=6x4x26 = 6x - 4x - 2 Simplify the terms on the right: 6=2x26 = 2x - 2

Step 3: Isolate the xx-term.

Add 2 to both sides: 6+2=2x6 + 2 = 2x 8=2x8 = 2x

Step 4: Solve for xx.

Divide both sides by 2: x=82=4x = \frac{8}{2} = 4

So, the solution is x=4x = 4.

Would you like more details or have any questions?

Here are 5 related questions to further explore:

  1. How do you solve similar equations with fractions or decimals?
  2. What happens if we swap the left and right sides of the equation at the start?
  3. Can we solve quadratic equations using a similar method of simplification?
  4. How do you check if your solution to a linear equation is correct?
  5. How would the solution process differ if the equation had no solution or infinite solutions?

Tip: Always double-check your answer by plugging it back into the original equation to verify!

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Algebra
Linear Equations
Simplification

Formulas

Rearranging terms to isolate variables
Simplification of linear expressions

Theorems

Properties of Equality

Suitable Grade Level

Grades 8-10